People´s Republic of China at the United Nations-voting and how it corresponds to Chinese foreign policy - Vedralová, Zuzana (2014)
This thesis focuses on the correlation of the UNSC voting behaviour of the People's Republic of China and its foreign policy. China's importance as a global power at the platform of the UN has been rising ever since 1971, the year of China's admittance as a new member of the UN and more importantly also the permanent member of the Security Council with the power of veto. Given that the veto power strongly influences the actions of the UNSC, its use has served as a major indicator of what issues are considered as most unfavourable and threatening to China's national interests and foreign policy goals. This thesis elaborates on the development of the foreign policy of China, which has changed significantly since the year of its acquired UN membership but has also kept many principles, present even before the establishment of the People's Republic of China in 1949. By specifically concentrating on the individual cast vetoes, also considering the use of a so-called hidden veto and the reasons behind them being cast, this thesis tries to find out, how China has been using its veto power with regards to its declared foreign policy objectives within the UN Security Council.